Contribution of smallholder farmers to food security and opportunities for resilient farming systems - Kapari, Mpho; Hlophe-Ginindza, Samkelisiwe; Nhamo, Luxon; Mpandeli, Sylvester (Frontiers in Sustainable Food Systems, 2023)
Climate change poses challenges that negatively affect smallholder farmers’ contribution to food security in sub-Saharan Africa. Consequently, countries from this region have the responsibility to reduce green gas emissions and adapt to the changing climate in the agricultural sector through such measures as climate-smart agriculture (CSA). This systematic review provides an overview of the CSA adoption challenges faced by smallholder farmers towards ensuring food security as well as recommendations to upscale CSA practices uptake. The review focuses on smallholder farmers of sub-Saharan Africa. Data collection for formal systematic reviews followed the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. Information was gathered from peer-reviewed articles with no limit to the year of publication. A total of 58 papers from the Web of Science and Scopus databases were included in the analysis. Results reveal that more research efforts need to be exerted towards the very vulnerable Southern Africa. The adoption of innovative agricultural practices should focus on rainwater harvesting and mulching while other CSA practices such as crop diversification and crop rotation show a high number of practices. However, major challenges facing smallholder farmers are financial availability, access to information and farm size. These hinder stallholder farmers’ ability to contribute to food security. As such, authors have recommended policy intervention, knowledge dissemination and capacity building as possible measures to get smallholder farmers on the right path to sustainable food production and CSA practices uptake.